Cross-task and cross-manipulation stability in shifting the decision criterion. Issue 5 (28th May 2018) - Frithsen, Amy; Kantner, Justin; Lopez, Brian A.; Miller, Michael B.
ABSTRACT: In recognition memory experiments participants must discriminate between old and new items, a judgment influenced by response bias. Research has shown substantial individual differences in the extent to which people will strategically adjust their response bias to diagnostic cues such as the prior probability of an old item. Despite this significant between subject variability, shifts in bias have been found to be relatively predictive within individuals across memory tests. Experiment 1 sought to determine whether this predictability extends beyond memory. Results revealed that the amount a subject shifted response bias in a recognition memory task was significantly predictive of shifting in a visual perception task, suggesting that shifting can generalise outside of a specific testing domain. Experiment 2 sought to determine how predictive shifting would be across two manipulations well known to induce shifts in bias: a probability manipulation and a response payoff manipulation. A modest positive relationship between these two methods was observed, suggesting that shifting behaviour is relatively predictive across different manipulations of shifting. Overall, results from both experiments suggest that response bias shifting, like response bias setting, is a relatively stable behaviour within individuals despite changes in test domain and test manipulation.